Study of Facade Characteristics of Limpapeh Bridge as an Iconic Building in Bukittinggi City - Widi Alparuki; Rinaldi Misa; Eri Saputra (Faculty of Engineering, Malikussaleh University, 2024)
Bukittinggi City is a city in West Sumatra that has high historical value and has iconic buildings, one of which is the Limpapeh Bridge as the pride of the community so that it must be preserved. This research aims to find out the characteristics of the building and the elements that influence it. The method uses descriptive qualitative by conducting observations, surveys, interviews, and documentation. Based on the analysis of the facade of Limpapeh bridge in terms of facade elements and facade composition. Viewed from the facade elements, Limpapeh Bridge has a strong cultural character with bagonjong roof shape and typical Minangkabau cultural ornaments from nature and plant motifs while the overall wall of the Limpapeh bridge looks plain with a dominant yellow colour so as to give a neutral feel to the building. The building door is a double door with no windows and a triangular gevel shape, railing with rectangular and circular shapes and there are two columns in the building. While the composition of the Limpapeh bridge facade has a formal and slightly monotonous character with a symmetrical balance, static rhythm, vertical rectangular geometry, the proportion of the width of the building is longer than the height of the building and has a dominance of discordant contrast.